2003
DOI: 10.1103/physreva.67.042712
|View full text |Cite
|
Sign up to set email alerts
|

Singular inverse square potential, limit cycles, and self-adjoint extensions

Abstract: We study the radial Schroedinger equation for a particle of mass m in the field of a singular attractive α/r 2 potential with 2mα > 1/4. This potential is relevant to the fabrication of nanoscale atom optical devices, is said to be the potential describing the dipole-bound anions of polar molecules, and is the effective potential underlying the universal behavior of three-body systems in nuclear physics and atomic physics, including aspects of Bose-Einstein condensates, first described by Efimov. New results i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
76
0
4

Year Published

2004
2004
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 78 publications
(81 citation statements)
references
References 24 publications
1
76
0
4
Order By: Relevance
“…In two previous studies of the 1/r 2 potential using renormalization theory, the regularization potential was chosen to be a spherical square well [11,12]:…”
Section: Square-well Regularizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In two previous studies of the 1/r 2 potential using renormalization theory, the regularization potential was chosen to be a spherical square well [11,12]:…”
Section: Square-well Regularizationmentioning
confidence: 99%
“…The simplest example is the quantum mechanics of a particle in a potential whose long-range behavior is 1/r 2 . This problem has been studied previously within the renormalization group framework by two different groups using a spherical square-well regularization potential [11,12]. Beane et al [11] showed that there are infinitely many choices for the coupling constant of the square-well potential, including a continuous function of the shortdistance cutoff R and a log-periodic function of R with discontinuities which corresponds to an RG limit cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, in the core renormalization framework , the strength ℵ of the regularizing core is promoted to a running coupling ℵ = ℵ(a), while the conformal coupling λ remains fixed [22,23]. In this framework, our unified description leads to…”
Section: Intrinsic and Core Renormalization Frameworkmentioning
confidence: 99%
“…(17) provides the characteristic logperiodic running coupling ℵ(a) of the core-the celebrated limit cycle for the renormalization group of the three-body problem [22,23,24]. For d = 3, l = 0, and zero energy,…”
Section: Intrinsic and Core Renormalization Frameworkmentioning
confidence: 99%